Clinical study on the efficacy of postural control combined with electroacupuncture in treating dysphagia after stroke - Wu, Yanli; Zhang, Zhongwen; Li, Qing; Yuan, Xiu; Ren, Jiange; Chen, Yulin; Zhu, He (Frontiers in Neurology, 2024)
Objective To evaluate the clinical effectiveness of combining postural control with electroacupuncture in the treatment of dysphagia following stroke, with the goal of establishing a solid clinical foundation for this therapeutic approach and investigating potential mechanisms to stimulate additional research and progress in post-stroke dysphagia management. Methods 138 patients who met the diagnostic and inclusion criteria were enrolled and divided into control group and observation group. Both groups received conventional rehabilitation training. Additionally, the control group received swallowing training and diet optimize, while the observation group received swallowing training, diet optimize, posture control as well as electroacupuncture therapy. After four weeks, swallowing function was assessed and compared between the two groups using the Standardized Swallowing Assessment (SSA) score and water swallowing test (WST). Results Patients who underwent postural control therapy in combination with electroacupuncture demonstrated significantly higher treatment efficacy compared to the control group. Notably, The SSA score and WST score in both groups decreased significantly, and the observation group showed more improvements in aspiration compared to the control group. Conclusion The integration of posture control, electroacupuncture, and conventional rehabilitation training can effectively lower the degree of post-stroke swallowing disorders, restore swallowing function, and significantly reduce the occurrence of complications such as aspiration, fever, and nutritional disorders. Moreover, this approach significantly improves the quality of life of patients and is more effective than conventional rehabilitation training in treating post-stroke swallowing disorders. Clinical trial registration https://www.chictr.org.cn/, Identifier ChiCTR2300075870.